Права дитини як об’єкт правової охорони держави - Коломоєць, Н. В.; Kolomoiets, N. V.; ORCID: http://orcid.org/0000-0003-4623-610X; Коломоєць, П. В.; Kolomoiets, P. V.; ORCID: http://orcid.org/0000-0001-8937-4698 (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 29-34, 2016)
Досліджено проблеми правової охорони прав дитини в Україні, наголошено, що, незважаючи на різноманіття нормативно-правового регулювання, права дитини залишаються другорядною категорією, на яку звертають увагу в останню чергу. Тому за результатами дослідження запропоновано організаційно-правові напрямки вдосконалення захисту прав дитини в Україні.

The problems of legal protection of child rights in Ukraine have been studied; it has been noted that despite the diversity of legal regulation, child rights remain secondary categories, which are considered to the last. It has been indicated that the child is nominal social unit of building civil society and it is impractical to neglect the rights from economic, political and legal points of view, as healthy, educated, protected child is the key to the development of real legal state. The authors by the results of the study have suggested organizational and legal ways of improving child rights protection in Ukraine, including: 1) systematization of legislation in the sphere of protecting child rights; 2) formation of an effective system of state authorities, which competences will include only ensuring, realization and protection of child rights; 3) formation of a special control group of the representatives of state authorities and the public, who will monitor the performance of the powers of the listed above authorities in the sphere of protecting child rights and supervising over the procedure of using budgetary funds for the implementation of child rights in the context of performing national, regional and local programs in protecting child rights.

Исследованы проблемы правовой охраны прав ребёнка в Украине, отмечено, что, несмотря на многообразие нормативно-правового регулирования, права ребёнка остаются второстепенной категорией, на которую обращают внимание в последнюю очередь. Поэтому по результатам исследования предложены организационно-правовые направления совершенствования защиты прав ребёнка в Украине.
Child rights as an object of legal protection of the state
Права ребёнка как объект правовой охраны государства
Коломоєць, Н. В. Права дитини як об’єкт правової охорони держави / Н. В. Коломоєць, П. В. Коломоєць // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 29-34.
Коломоєць Н. В., Коломоєць П. В. "Права дитини як об’єкт правової охорони держави." Вісник Харківського національного університету внутрішніх справ 4 (2016): 29-34.
Kolomoiets, N.V. and Kolomoiets, P.V. (2016), “Child rights as an object of legal protection of the state” [Prava dytyny yak obiekt pravovoi okhorony derzhavy], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 29–34.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; дитина; права дитини; правова охорона; захист прав дитини; державна політика; child rights; legal protection; protection of child rights; state policy; права ребёнка; правовая охрана; защита прав ребёнка; государственная политика; ребёнок; child